2011
DOI: 10.1111/j.1464-0597.2011.00470.x
|View full text |Cite
|
Sign up to set email alerts
|

Antecedents of Underemployment: Job Search of Skilled Immigrants in Canada

Abstract: We investigate factors that skilled immigrants can improve in order to have better job search outcomes, in particular to avoid underemployment. We test an unfolding model which considers barriers faced by skilled immigrants during their job search (language and cultural barriers, and the lack of social support in the receiving country), job search constructs and job search outcomes (including underemployment). We collected data through an online questionnaire and obtained 357 usable responses from skilled immi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(52 citation statements)
references
References 49 publications
1
51
0
Order By: Relevance
“…For example, studies show that building a social network and putting conscious effort to accumulate cultural and social capital for career self-management, (e.g. learning the local language), significantly helped the job search process of immigrants (Fang et al, 2013;George et al, 2012;Guerrero and Rothstein, 2012;Pearson et al, 2012;Tharmaseelan et al, 2010;Winterheller and Hirt, 2017). Researchers also found that, when other tactics failed, getting a formal education in the host country sometimes served as 'an entry ticket' to the job market (George et al, 2012;Winterheller and Hirt, 2017).…”
Section: Research On High-skilled Immigrantsmentioning
confidence: 99%
“…For example, studies show that building a social network and putting conscious effort to accumulate cultural and social capital for career self-management, (e.g. learning the local language), significantly helped the job search process of immigrants (Fang et al, 2013;George et al, 2012;Guerrero and Rothstein, 2012;Pearson et al, 2012;Tharmaseelan et al, 2010;Winterheller and Hirt, 2017). Researchers also found that, when other tactics failed, getting a formal education in the host country sometimes served as 'an entry ticket' to the job market (George et al, 2012;Winterheller and Hirt, 2017).…”
Section: Research On High-skilled Immigrantsmentioning
confidence: 99%
“…Previous research has identified various barriers for immigrants to obtain positions commensurate with their qualifications. These include lack of language fluency, cultural knowledge and social contacts (Guerrero & Rothstein, 2012; Johnston, Khattab, & Manley, 2015) as well as lack of recognition of foreign degrees and experiences (Hakak, Holzinger, & Zikic, 2010; Zikic, Bonache, & Cerdin, 2010). However, studies have shown that these barriers do not fully explain overqualification among immigrants and have concluded that also discrimination might play a role (Duvander, 2001; Støren & Wiers-Jenssen, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to controlling for gender, age, type of contract (part-time vs. full-time) and average working hours per week, English proficiency will be assessed. To that end we will use the three-item scale validated by Guerrero and Rothstein (2012) that measures ability to speak, read, and write in English, using a 10-point scale ranging from 1, extremely poor, to 10, excellent. Additionally, participants will have to position their English reading ability based on the six anchors, ranging from A1 to C2, described by the reading dimension of the Common European Framework of Reference for Languages (Verhelst et al, 2009).…”
Section: Methodsmentioning
confidence: 99%